Bimetallic hexanuclear clusters in Ce/Zr-UiO-66 MOFs: in situ FTIR spectroscopy and modelling insights. Issue 18 (21st April 2020) - Atzori, Cesare; Lomachenko, Kirill A.; Jacobsen, Jannick; Stock, Norbert; Damin, Alessandro; Bonino, Francesca; Bordiga, Silvia
Abstract : In situ FTIR and DFT modelling were used to study the stoichiometry of the hexanuclear clusters in Ce/Zr-UiO-66 compounds. Abstract : In situ FTIR spectroscopy in combination with results from DFT calculations was used to determine the composition of mixed-metal clusters Ce x Zr6− x (μ3 -O)4 (μ3 -OH)4 in Ce/Zr-UiO-66 compounds. Detailed, quantitative evaluation of vibrational bands ν (OH) of (μ3 -OH)Ce x Zr3− x groups allowed us to distinguish between two possible models: a solid solution or the presence of distinct clusters. This relatively straightfoward method should be also transferable to other mixed-metal metal–organic frameworks (MOFs).